Economic and industrial assessment of common plum and cherry plum in the foothill zone of Adygea - V. V. Sherstobitov (Новые технологии)
The article contains materials of the research on the yield of common plum and cherry plum varieties. The most productive samples have been selected. The productivity of the selected varieties have been studied for four years, which includes the following characteristics: average productivity (kg/tree), average productivity from one cubic meter of a crown (kg/m3 ), average fruit weight (g), average productivity (% to the standard). The economic efficiency of common plum and cherry plum for a 5 years period has been studied. The following indicators have taken into account: yield (t/ha), product cost (rubles/ha), production costs (rubles/ha), sales profit (rubles/ha), product profitability (%). It has been found that the productivity of the studied varieties (kg/tree) is quite different. Common plum productivity varies from from 14,4 (Nectar) to 34,6 (Shamsi). That of cherry plum varies from 20 (Rioni) to 34,1 (Shuntukskaya 11). Mathematical processing of data on the yield of fruits of common plum and cherry plum has been carried out using the method of field experiment. Statistical processing of one-factor experiment has been carried out by the method of deviation from the average one according to the variant. 3 groups of plum and cherry plum varieties have been identified at the standard level: low-productive, medium-productive, high-productive. The varieties of cherry plum with high productivity from one cubic meter of crown, more than 2,0 kg/m3 , have been identified: early Niberdzhaevskaya (st), Most early, Shuntukskaya 9, Shuntukskaya 11, Klyukovka, large Nalchikskaya. These include the following varieties of common plum: Renklod Altana, early Kabardinskaya (st), Vascova, Arvita, Hungarian Italian, Anna Shpet (st). The studied varieties of plum and cherry plum are divided into groups according to fruit sizes: small-fruited, medium-fruited and large-fruited. It has been established that the economic efficiency of the production of common plum and cherry plum fruits mainly depends on the yield of the variety and the cost of production. The profitability of common plum varieties is from 59,7% to 130%, cherry plum – from 39,9% to 59,2%.Economic and industrial assessment of common plum and cherryplum in the foothill zone of Adygea.